2021
DOI: 10.1186/s12884-021-04224-3
|View full text |Cite
|
Sign up to set email alerts
|

Acceptance of seasonal influenza vaccination and associated factors among pregnant women in the context of COVID-19 pandemic in China: a multi-center cross-sectional study based on health belief model

Abstract: Background Seasonal influenza can circulate in parallel with coronavirus disease (COVID-19) in winter. In the context of COVID-19 pandemic, the risk of co-infection and the burden it poses on healthcare system calls for timely influenza vaccination among pregnant women, who are the priority population recommended for vaccination. We aimed to evaluate the acceptance of influenza vaccination and associated factors among pregnant women during COVID-19 pandemic, provide evidence to improve influenz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
22
1
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 44 publications
6
22
1
1
Order By: Relevance
“…In both univariable and multivariable analyses, most constructs in HBM models were significantly associated with vaccination intentions for a third dose of COVID-19. Our results are generally consistent with previous studies in China on the impact of health beliefs on vaccination acceptance [17,18,20]. Baccolini et al found higher perceived COVID-19 severity was negatively associated with vaccine hesitancy (aOR = 0.89, 95% CI: 0.85-0.94) among Italian university students [22].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…In both univariable and multivariable analyses, most constructs in HBM models were significantly associated with vaccination intentions for a third dose of COVID-19. Our results are generally consistent with previous studies in China on the impact of health beliefs on vaccination acceptance [17,18,20]. Baccolini et al found higher perceived COVID-19 severity was negatively associated with vaccine hesitancy (aOR = 0.89, 95% CI: 0.85-0.94) among Italian university students [22].…”
Section: Discussionsupporting
confidence: 92%
“…Based on our previous COVID-19 vaccination willingness questionnaire [17,18], we specifically focused on the acceptance of the third dose of COVID-19 vaccine and its associated factors with health beliefs in this study. we investigated information including basic personal characteristics, attitudes towards a third dose of COVID-19 vaccine, knowledge of COVID-19 infection and vaccines, and vaccine-related health beliefs.…”
Section: Data Collectionmentioning
confidence: 99%
See 1 more Smart Citation
“…The HBM has been used to evaluate health behaviors in various contexts, and the use of HBM with pregnant women's acceptance of vaccines is not novel. Few studies have examined pregnant women's acceptance of the influenza vaccine while pregnant [18,19] and others have used the HBM to assess acceptance of the Pertussis vaccine while pregnant [20]. In China, researchers applied the HBM to pregnant women's COVID-19 vaccine intentions [21].…”
Section: Health Belief Modelmentioning
confidence: 99%
“…The main relationships of interest were motivated on the basis of Health Belief Model (HBM). HBM empowers researchers to explain and predict health promoting behaviour in terms of patterns of belief by addressing the association between personal threat of an illness or disease and health services utilisation [ 46 – 48 ]. Facing the susceptible risk of COVID-19 pandemic, the public population with new health conditions would like to perform care/treatment-seeking behaviors when considering the related severity and barriers.…”
Section: Introductionmentioning
confidence: 99%